Specialist health care services use in a European cohort of infants born very preterm - Seppänen, AV (2019)
Aim Children born very preterm require additional specialist care because of the health and developmental risks associated with preterm birth, but information on their health service use is sparse. We sought to describe the use of specialist services by children born very preterm in Europe. Method We analysed data from the multi-regional, population-based Effective Perinatal Intensive Care in Europe (EPICE) cohort of births before 32 weeks’ gestation in 11 European countries. Perinatal data were abstracted from medical records and parents completed a questionnaire at 2 years corrected age (4322 children; 2026 females, 2296 males; median gestational age 29wks, interquartile range [IQR] 27–31wks; median birthweight 1230g, IQR 970–1511g). We compared parent-reported use of specialist services by country, perinatal risk (based on gestational age, small for gestational age, and neonatal morbidities), maternal education, and birthplace. Results Seventy-six per cent of the children had consulted at least one specialist, ranging across countries from 53.7% to 100%. Ophthalmologists (53.4%) and physiotherapists (48.0%) were most frequently consulted, but individual specialists varied greatly by country. Perinatal risk was associated with specialist use, but the gradient differed across countries. Children with more educated mothers had higher proportions of specialist use in three countries. Interpretation Large variations in the use of specialist services across Europe were not explained by perinatal risk and raise questions about the strengths and limits of existing models of care.